MeerKAT discovery of radio emission from the Vela X-1 bow shock. Issue 1 (24th November 2021) - van den Eijnden, J; Heywood, I; Fender, R; Mohamed, S; Sivakoff, G R; Saikia, P; Russell, T D; Motta, S; Miller-Jones, J C A; Woudt, P A
ABSTRACT: Vela X-1 is a runaway X-ray binary system hosting a massive donor star, whose strong stellar wind creates a bow shock as it interacts with the interstellar medium (ISM). This bow shock has previously been detected in H α and infrared, but, similar to all but one bow shock from a massive runaway star (BD+43 o 3654), has escaped detection in other wavebands. We report on the discovery of 1.3 GHz radio emission from the Vela X-1 bow shock with the MeerKAT telescope. The MeerKAT observations reveal how the radio emission closely traces the H α line emission, both in the bow shock and in the larger scale diffuse structures known from existing H α surveys. The Vela X-1 bow shock is the first stellar-wind-driven radio bow shock detected around an X-ray binary. In the absence of a radio spectral index measurement, we explore other avenues to constrain the radio emission mechanism. We find that thermal/free–free emission can account for the radio and H α properties, for a combination of electron temperature and density consistent with earlier estimates of ISM density and the shock enhancement. In this explanation, the presence of a local ISM overdensity is essential for the detection of radio emission. Alternatively, we consider a non-thermal/synchrotron scenario, evaluating the magnetic field and broad-band spectrum of the shock. However, we find that exceptionally high fractions (≳ 13 per cent) of the kinetic wind power would need to be injected into the relativistic electron population to explain the radio emission. Assuming lower fractions implies a hybrid scenario, dominated by free–free radio emission. Finally, we speculate about the detectability of radio bow shocks and whether it requires exceptional ISM or stellar wind properties.